Plant‐produced viral bovine vaccines: what happened during the last 10 years? - Ruiz, Vanesa (2015)
Vaccination has proved to be an efficient strategy to deal with viral infections in both human and animal species. However, protection of cattle against viral infections is still a major concern in veterinary science. During the last two decades, the development of efficient plant‐based expression strategies for recombinant proteins prompted the application of this methodology for veterinary vaccine purposes. The main goals of viral bovine vaccines are to improve the health and welfare of cattle and increase the production of livestock, in a cost‐effective manner. This review explores some of the more prominent recent advances in plant‐made viral bovine vaccines against foot‐and‐mouth disease virus (FMDV), bovine rotavirus (BRV), bovine viral diarrhoea virus (BVDV), bluetongue virus (BTV) and bovine papillomavirus (BPV), some of which are considered to be the most important viral causative agents of economic loss in cattle production.